2015
DOI: 10.1016/j.jff.2015.04.044
|View full text |Cite
|
Sign up to set email alerts
|

A bioactive formulation based on Fragaria vesca L. vegetative parts: Chemical characterisation and application in κ-carrageenan gelatin

Abstract: Available online A B S T R A C TA bioactive formulation based on the vegetative parts of the wild strawberry, Fragaria vesca L., was developed by using a microencapsulated extract (lyophilised infusion form). For that purpose, a process based on an atomisation/coagulation technique with alginate as the wall material was applied. Among the tested hydromethanolic and aqueous extracts, both obtained from wild and commercial samples, the infusion of a wild species emerged as the most antioxidative one. The higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
2
19
0
1
Order By: Relevance
“…15 The alginate was already reported as a suitable coating material to protect bioactive natural extracts by microencapsulation, aiming at their incorporation in foods. 16,17 Stojanovic et al 18 studied the alginate encapsulation of aqueous thyme extracts also rich in rosmarinic acid and many polyphenolic compounds similar to rosemary extract; the authors reported the potential of using a hydrogel material for encapsulation of natural compounds to improve their functionality and stability in food products. Another formulation with alginate and rosemary are coating films to inhibit lipid oxidation and the warmed-over flavor formation (WOF) in pre-cooked meats.…”
Section: Introductionmentioning
confidence: 99%
“…15 The alginate was already reported as a suitable coating material to protect bioactive natural extracts by microencapsulation, aiming at their incorporation in foods. 16,17 Stojanovic et al 18 studied the alginate encapsulation of aqueous thyme extracts also rich in rosmarinic acid and many polyphenolic compounds similar to rosemary extract; the authors reported the potential of using a hydrogel material for encapsulation of natural compounds to improve their functionality and stability in food products. Another formulation with alginate and rosemary are coating films to inhibit lipid oxidation and the warmed-over flavor formation (WOF) in pre-cooked meats.…”
Section: Introductionmentioning
confidence: 99%
“…There are some documented examples dealing with the application of microencapsulation to natural extracts for use in functional foods . Our research group has successfully encapsulated Fragaria vesca L. (Dias, Barros et al, 2015) and Rubus ulmifolius Schott (Martins et al, 2014) extracts that were further incorporated into j-carrageenan gelatin and yogurts, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Rosa canina (Guimarães et al, 2013b), Juglans regia , Rubus ulmifolius (Martins et al, 2014a), Fragaria vesca (Dias et al, 2015), Pimpinella anisum , Coriandrum sativum , Melissa officinalis , Foeniculum vulgare (Caleja et al, 2015), Matricaria recutita (Guimarães et al, 2013a), Echinacea purpurea (Pires et al, 2016) and Pterospartum tridentatum (Roriz et al, 2014) extracts were previously chemically characterized by our research group. In the present study, we performed the characterization of the most active extract.…”
Section: Phenolic Compounds Analysismentioning
confidence: 99%